Finite sequent calculi for PLTL - Romas Alonderis; Regimantas Pliuškevičius; Aida Pliuškevičienė (Lietuvos Matematikos Rinkinys, 2015)
Two sequent calculi for temporal logic of knowledge are presented: one containing invariant-like rule and the other containing looping axioms. Its proved that the calculi are equivalent, sound and complete.